Respuesta :

Answer:

x = 4 , y = -6 thus: D.) is the answer

Step-by-step explanation:

Solve the following system:

{y = -x/4 - 5 | (equation 1)

y = 10 - 4 x | (equation 2)

Express the system in standard form:

{x/4 + y = -5 | (equation 1)

4 x + y = 10 | (equation 2)

Swap equation 1 with equation 2:

{4 x + y = 10 | (equation 1)

x/4 + y = -5 | (equation 2)

Subtract 1/16 × (equation 1) from equation 2:

{4 x + y = 10 | (equation 1)

0 x+(15 y)/16 = -45/8 | (equation 2)

Multiply equation 2 by 16/15:

{4 x + y = 10 | (equation 1)

0 x+y = -6 | (equation 2)

Subtract equation 2 from equation 1:

{4 x+0 y = 16 | (equation 1)

0 x+y = -6 | (equation 2)

Divide equation 1 by 4:

{x+0 y = 4 | (equation 1)

0 x+y = -6 | (equation 2)

Collect results:

Answer: {x = 4 , y = -6

Answer:

I think it's b

Step-by-step explanation:

because y × x and 22/4